A clinical study of post operative complications of Lichtenstein’s hernioplasty for inguinal hernia - Vasu, S.; Sagar, Kshir (International Surgery Journal, 2018)
Background: Lichtenstein’s hernioplasty is the commonly done surgery for inguinal hernias. The study was done with the objective to evaluate the postoperative complications, and the recurrence rate associated with Lichtenstein’s hernioplasty. Methods: This was a prospective clinical study conducted at Sapthagiri Institute of Medical Science and Research Centre, Bangalore during the period from May 2015 to April 2016. A total of 50 patients with inguinal hernia were included in the study. All the patients underwent Lichtenstein’s hernioplasty. Outcome of the surgery was evaluated by the incidence of postoperative complications and recurrence rate of hernia after 1 year follow up. Results: Intraoperative complications were observed in 3 (6%) patients. Immediate postoperative complication was seen in 6 (12%) cases. Stiffness in lower abdomen was noticed in 13 (26%) cases. The average post-operative hospital stay was 4.06±1.43 days and the average post-operative ambulation time was 1.52±0.64 days. The average time taken to return to work post-operatively was 8.68±2.63 days. Long term complications included are foreign body sensation and chronic pain at operated site. After 1 year follow up the prevalence of both the complications was decreased to 4% and 6% respectively. No recurrence of hernia (0%) was noticed after 1 year follow up. Conclusions: Lichtenstein’s hernioplasty was considered as the best surgical procedure for inguinal hernia repair because of low recurrence rate (0%) and postoperative complications.